2022
DOI: 10.2807/1560-7917.es.2022.27.44.2101144
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1 colistin resistance gene sharing between Escherichia coli from cohabiting dogs and humans, Lisbon, Portugal, 2018 to 2020

Abstract: Background The emergence of colistin resistance is a One Health antimicrobial resistance challenge worldwide. The close contact between companion animals and humans creates opportunities for transmission and dissemination of colistin-resistant bacteria. Aim To detect potential animal reservoirs of colistin-resistant Escherichia coli and investigate the possible sharing of these bacteria between dogs, cats and their cohabiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The intimate relationship between pets and owners potentially represents a public health concern in terms of AMR gene development and transmission (190). Indicative evidence has been provided in several studies where AMR genes present in fecal samples of humans and their companion animals were characterized (191)(192)(193). In a more comprehensive metagenomic study, Zhao et al (194) compared the gut AMR genes, the MGEs and the microbiota among dogs and their owners as well as kennel dogs.…”
Section: Exchange Of Microbiota Between Pets and Humansmentioning
confidence: 99%
“…The intimate relationship between pets and owners potentially represents a public health concern in terms of AMR gene development and transmission (190). Indicative evidence has been provided in several studies where AMR genes present in fecal samples of humans and their companion animals were characterized (191)(192)(193). In a more comprehensive metagenomic study, Zhao et al (194) compared the gut AMR genes, the MGEs and the microbiota among dogs and their owners as well as kennel dogs.…”
Section: Exchange Of Microbiota Between Pets and Humansmentioning
confidence: 99%
“…However, there are also complicating factors in some countries. For example, a certain amount of third-and fourth-generation cephalosporins may also be used in the treatment of companion animals, (Hur et al, 2020;Méndez & Moreno, 2020) especially cats (Mateus et al, 2011), i.e. animals that are not producing food and not included in the resistance monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Mcr genes have been found in similar plasmids in the same bacterial species isolated from food‐producing animals, food, humans and the environment, indicating the possibility for transmission between the compartments (Lima et al., 2019; Skov & Monnet, 2016). A recent study identified indistinguishable MDR E. coli ST744 harbouring mcr ‐ 1 from humans and dogs in the same household; however, studies in Germany in turkeys, pigs and farm personnel did not identify clonality between the human and animal mcr‐1 ‐positive E. coli isolates from the same farms (Effelsberg et al., 2021; Menezes et al., 2022; Nordhoff et al., 2023). Due to lack of data on the human side the potential association of resistance in isolates from food‐producing animals and isolates from humans cannot yet be estimated in this JIACRA report.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since 2020, there have been more than 20 notifications or recalls of pet food and RMBD in the EU due to the detection of zoonotic pathogens, particularly Salmonella and pathogenic Escherichia coli [8], and also cases of human infections with Salmonella and Shiga toxin-producing E. coli (STEC) linked to exposure to RMBDs [9][10][11]. Several studies have also established a correlation between the microbiota of pets and their owners, including the presence of antibiotic-resistant strains, with pet food as a potential source [12,13]. However, certain antibiotic-resistant bacteria and genes of public health concern, such as the mcr gene conferring resistance to the last-line antibiotic colistin, have not been extensively studied in pet food and RMBDs [1,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%